Novel configurations for a citrus waste based biorefinery: from solventless to simultaneous ultrasound and microwave assisted extraction. Issue 24 (31st October 2016) - González-Rivera, J.; Spepi, A.; Ferrari, C.; Duce, C.; Longo, I.; Falconieri, D.; Piras, A.; Tinè, M. R.
Abstract : Innovative extraction configurations for the biorefining of a biomass waste (citrus peel) were developed in this work. Abstract : Innovative extraction configurations for the biorefining of a biomass waste (citrus peel) were developed in this work. Non-conventional energies, such as microwaves (MW) and ultrasounds (US), were directly irradiated to the fresh orange peel using a versatile MW coaxial dipole antenna. This particular MW configuration enabled us to build two new extraction systems: (1) a coaxial solventless MW-assisted extraction (SMWAE) approach and, (2) a simultaneous ultrasound coaxial MW-assisted hydrodistillation (US-MWHD) method. The yield and chemical composition of the essential oils (EOs) of the orange peel obtained by the two innovative approaches were analyzed as a function of the extraction time and compared with those from coaxial microwave hydrodistillation (MWHD) and conventional hydrodistillation (CH). The EOs were chemically characterized by GC and GC-MS analysis. The residue mash was then used to extract pectin by a MW-assisted procedure. The structure and thermal stability of the pectin were investigated by FTIR and TG. The biorefining of EOs and pectin from a citrus waste maximises the benefits of our proposed green methodologies, which involve safe operability, faster processing and easy scalability. Furthermore, the energy consumed per unit mass of products in each step of the orange peel biorefining clearly showed that the most promising approach is SMWAE (since it is around 27 times lower than the CH approach). MWHD and US-MWHD also showed more than 60% energy savings compared to CH.